2016
DOI: 10.7860/jcdr/2016/15159.7558
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Myofibroblastic Tumour of Thyroid with its Prominent Spindle Cell Pattern: A Rare Case Report

Abstract: A 61-year-old male patient presented with painless thyroid swelling for 2 years duration. He was clinically euthyroid and his thyroid profile was normal. Ultrasound showed hypo echoic thyroid mass in the right lobe with cystic degeneration. FNAC [ Inflammatory myofibroblastic tumour of thyroid is very rare. Only 18 cases reported so far. Here we report a case of Inflammatory myofibroblastic tumour with its prominent spindle cell (fibrohistiocytic) pattern in a 61-year-old male patient. The dominant histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We found from our search of the English literature using the term IMTs of the thyroid, that there were 22 such reported cases. For all, the diagnosis was PCG and only five cases involved IMTs or inflammatory pseudotumors [13,[21][22][23][24]. These reports indicated that IMTs of the thyroid differ from those at other anatomic sites and are often negative for ALK-1.…”
Section: Introductionmentioning
confidence: 91%
“…We found from our search of the English literature using the term IMTs of the thyroid, that there were 22 such reported cases. For all, the diagnosis was PCG and only five cases involved IMTs or inflammatory pseudotumors [13,[21][22][23][24]. These reports indicated that IMTs of the thyroid differ from those at other anatomic sites and are often negative for ALK-1.…”
Section: Introductionmentioning
confidence: 91%
“…3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] We found 3 cases (cases 19-21 in Table 1) reported as IMT of the thyroid (IMT-T) that were lesions containing predominantly myofibroblastic proliferation with an associated polymorphous inflammatory infiltrate. [21][22][23] The clinicopathologic features are summarized in Table 1. Comparison of clinicopathologic characteristics of PCG-T and IMT-T is summarized in Table 2.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…6 On fine-needle aspiration in IMT-T, 1 case each was reported as epithelioid neoplasm (case 19) 21 and spindle cell proliferation (case 21). 23…”
Section: Microscopic Pathology Cytologymentioning
confidence: 99%
See 2 more Smart Citations